State of the peoples a global human rights report on societies in danger (Beacon Press, 1993)
The late twentieth century has taught us that indigenous peoples and ethnic minorities - from the Tawahka in Honduras to the Inuit of Canada to the Nyae Nyae of Southern Africa - have important cultural, environmental, and human rights lessons for us all. And yet these peoples are losing land, natural resources, and control over their lives as never before. State of the Peoples is the first comprehensive and up-to-the-minute report on the status of threatened indigenous peoples and ethnic minorities throughout the world. Included are the latest data from field researchers on hundreds of indigenous peoples, arranged by region; expert articles on critical issues facing Burma's indigenous women, the Penan in Borneo, Bosnian minorities, and more; more than 90 photographs, charts, and maps, plus a two-page map of societies in danger; and a Resources for Action section: a comprehensive and indispensable guide for activists, academics, and the press. State of the Peoples makes a strong case for group rights - the rights of a particular people to maintain its culture, religion, traditional lands, and collective control of natural resources. Indigenous voices are heard throughout: Winona LaDuke on Anishinabe cultivation of wild rice, ethnic Burmese women on systematic sexual abuse at the hands of the Tatmadaw army, and more. The book underlines the unavoidable connections between global environmental health and the rights of indigenous peoples. State of the Peoples is a powerful political tool in promoting action and highlighting strategies to prevent cultural loss. Cultural Survival, a highly visible research organization (and creator of Rainforest Crunch), has championed the human rights of indigenous peoples and ethnic minorities for twenty years.